Evaluation of renal near-infrared spectroscopy for predicting extubation outcomes in the pediatric intensive care setting - Colak, Mustafa; Ceylan, Gokhan; Topal, Sevgi; Sarac Sandal, Ozlem; Atakul, Gulhan; Soydan, Ekin; Sarı, Ferhat; Hepduman, Pinar; Karaarslan, Utku; Ağın, Hasan (Frontiers in Pediatrics, 2024)
In pediatric intensive care units, extubation failure following invasive mechanical ventilation poses significant health risks. Determining readiness for extubation in children can minimize associated morbidity and mortality. This study investigates the potential role of renal nearinfrared spectroscopy (RrSO2) in predicting extubation failure in pediatric patients.A total of 84 patients aged between 1 month and 18 years, mechanically ventilated for at least 24 hours, were included in this prospective study. RrSO2 levels were measured using nearinfrared spectroscopy before and during an extubation readiness test (ERT). The primary outcome measure was extubation failure, defined as a need for reintubation within 48 hours.Of the 84 patients, 71 (84.6%) were successfully extubated, while 13 (15.4%) failed extubation.RrSO2 was found to be lower in the failed extubation group, also decrease in RrSO2 values during ERT was significantly greater in patients with extubation failure. ROC analysis indicated a decrease in ΔRrSO2 of more than 6.15% from baseline as a significant predictor of extubation failure, with a sensitivity of 0.984 and a specificity of 0.889.Monitoring changes in RrSO2 values may serve as a helpful tool to predict extubation failure in pediatric patients. Further multi-center research is warranted to improve the generalizability and reliability of these findings.